IMPROVED POWER GRID STABILITY WITH REGULAR MAINTENANCE OF MEDIUM-VOLTAGE TRANSFORMER CONNECTIONS - Nisa', Silvi Nur Rakhman; Rohman, Miftahur; Baihaqi, Mochamad Faris (Indonesian Journal of Engineering and Technology (INAJET), 2025)
The power grid is a vital infrastructure that ensures the distribution of energy from the plant to the consumer. One of the important components in this network is the transformer, which regulates the voltage level as needed. In medium-voltage networks, transformer connections play a crucial role in maintaining system stability. Unmaintained connection conditions can cause disturbances in the form of decreased voltage quality, blackouts, and equipment damage. Unfortunately, connection maintenance is often done reactively, only when a fault occurs. This study aims to analyze the impact of routine maintenance of transformer connections on the stability of the power grid at PT PLN (Persero) UP3 South Surabaya – ULP Ngagel. The methods used include field observation, documentation of maintenance activities, and analysis of disturbance data before and after maintenance. The results of the study show that routine maintenance is able to reduce the frequency of connection failures, improve voltage stability, and extend the life of network components.